Implementation Of Character Education In Building Nationalism To Prevent Radicalism In Digital Era - Hendra Setiawan; Seriwati Ginting; Isabella Isthipraya Andreas; Priska Saviourien Adimercya (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
The more days of tolerance, the sense of solidarity and the rise of hate speech on social media, as well as the decline in national values, the fading of the national spirit is a serious concern, especially for educators. Indonesia is experiencing various challenges or threats. the best for the country is just a slogan. Society seems to have lost its direction (disorientation) in the life of the nation and state, due to the dim implementation of basic values. The basic value that becomes a reference or guideline is considered as something ancient. There are even organizations that oppose the existence of these basic values. It is unfortunate that the younger generation is also swept away, as if they have forgotten history. The growing trend in society prefers pragmatic and practical values which in reality are not in accordance with the soul and personality of the Indonesian nation. This study aims to examine and explore and provide an overview of character education which includes civic education courses, Pancasila education and character development courses for students at Maranatha Christian University. The implementation of these values was carried out by observing, interviewing, as well as questionnaires which were distributed to students. Interviews were also conducted with the civic education lecturer team, the Pancasila lecturer team, the character development lecturer team and educational institutions.The emphasis in this research underscores how advances in technology and information in the digital era can be implemented from personality development courses. Personality development is one of the targets of civics and Pancasila education courses and character development courses. Conventional learning that has been entrenched so far must be replaced with digital learning. It takes effort and creativity from lecturers so that the meaning and message of the values of civic education and Pancasila values can be accepted and carried out in life by students. The method or approach used in this research is descriptive qualitative through in-depth observation, even though it is constrained by a pandemic, it can be combined by conducting interviews both structured and open interviews, literature studies and documentation. The techniques used to examine the research are data collection, data reduction, data display and conclusions. For the output of the research team, it is planned to be published in an accredited journal.